A facilitator’s guide for nutrition training in Bangladesh: a training of trainers module - Parupalli, V.L. Bharathi; Parvin, Aklima; Mahjabin, Tasnima; Scott, Samuel P.; Cheesman, Stephanie; Rowshan, Radia; Krupnik, Timothy J. (TAFSSA, 2024)
In the context of nutrition sensitive agriculture, it's crucial to empower farmers with the right knowledge on producing crops to meet their nutritional requirements. This publication, 'A facilitator's guide for nutrition training in Bangladesh’ has been produced as a part of action research in the CGIAR Regional Integrated Initiative Transforming Agrifood Systems in South Asia (TAFSSA) that aims to deliver a coordinated program of research and engagement across the food production–to–consumption continuum to support equitable access to sustainable healthy diets, improve farmer livelihoods and resilience, and conserve land, air and groundwater resources. In our experience, not all farmers or farming communities have information on the ways in which the crops, livestock, and fish products they may produce are linked to nutrition outcomes. This training module is therefore a response to this important community-level information gap. The contents of this module have been systematically organized into six sessions, accompanied by illustrative examples of participatory teaching approaches to help the facilitators deliver the contents in an interactive way.